EFEKTIVITAS KINERJA PEGAWAI KEARSIPAN PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN SUMENEP - Alifia Nurien Maghfirah; Aryo Wibisono (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
State Civil Apparatus (ASN) is a profession of civil servants and government employees with work agreements binding themselves to government agencies. The purpose of this study was to determine the career journey system for ASN, problems with ASN career journeys related to job promotions and the causes of problems with career paths related to promotions in ASN at the Education Office of Sumenep Regency. The research method used is descriptive qualitative research. The results of the study show that the ASN career journey system there is generally assessed by the direct supervisor, namely the Head of the Service regarding his work performance, also seen from ASN personal data and 6 other indicators consisting of; Educational Qualifications; Position Track Record or Work Experience; Competence; Development History; History of Performance Assessment Results; Education & Training Experience and ASN age. Then the problems related to promotion of ASN positions with outstanding achievements are constrained so that it affects their career paths due to the lack of attention from the Sumenep Regency Government to competent and accomplished ASNs and the amount of competition between ASNs at the Sumenep Regency Education Office.